Electrophysiocardiogram: For the first time EPCG has been recorded on human body surface. (1st November 2016) - Chen, Gary; Yao, Lingling; Zhao, Ruiping; Zeng, Jianping; Liu, Ming
Abstract: Since ECG was invented in 1903, this is the first time in history that a full information multi-band and multi-linear electrophysiological cardiogram has been used to successfully scan and record on the human body surface. Since it is able to record various multi-band, multi-track linear electric signals of cardiac electrophysiological activities that correspond to different regions of the entire heart, it has thus been denominated as "electrophysiocardiogram" (EPCG). A traditional ECG is always represented by a characteristic wave form, which resembles a string. For a long period of time, ECG has had a lot of mysteries surrounding it, it maybe because ECG has a lot of mixed signals buried in such convolutionary forms, which limits the amount of the signals that are discernable and determinable. For the first time, the EPCG technology has allowed cardiac signals to be convoluted into the linear wave form, which is then processed through various new approaches featuring multiple frequency bands, multiple dimensions and multiple patterns, and consequentially recorded as the following types of signals within the ranges of P wave and T wave: multiple frequency band signals, signals of different regions and different locations, forward waves and negative waves. Therefore, EPCG may help to solve many puzzling scientific questions regarding heart, such as exactly how many electric signals are involved in heart excitation, pacing, conduction and action, as well as many other intriguing questions about heart, and thus would become a very helpful tool in clinical practice.